Specific Features of Forming Foreign Language Competence in Reading as a Method Of Students’ Independent Work - Shaposhnikova, Larysa (Pedagogical Discourse, 2013)
The article analyzes the problem of forming foreign language competence in reading in the context of organizing students’ effective independent work in the process of foreign language study. The motive for reading as a communicative activity is intercourse, and its goal is to provide the necessary information; thus, the work with the text may have different goals: sometimes one just needs to identify what the text is, in other cases it is important to understand the basic or new information, the author’s intention, the implication. Properly formed foreign language competence in reading helps students to work with textbooks and other educational books, contributes to the expansion of the students’ scientific knowledge and to the skills formation of independent cognitive activity. Such method is used to understand and strengthen scientific information already known by the students, as well as to gain knowledge independently without the help of the teacher. The properly formed skills of foreign language competence in reading also allow students to use different scientific works in foreign language not specified in educational plans, as well as to expand and deepen scientific knowledge on one’s own.